2-N-Acetylglucosamine-Î±-O-threonine, an amino acid derivative from the marine sponge Cinachyrella kuekenthali - Henríquez, Willian; Sevcik, Carlos; D”™SuzeGina; Visbal, Gonzalo; Christophersen, Carsten (Ciencia, 2014)
A new amino acid derivative, 2-N-acetylglucosamine- Î± -O-threonine [2-N-AcNGlc- Î± -O-Thr, (1)], was isolated from the marine sponge Cinachyrella kuekenthali. The structure assignment is based on interpretation of NMR spectroscopic data. The orientation of the Î± -O-glucosamine bond was deduced from the value of the (J = 3.7 Hz) coupling constant of the anomeric proton and the position of the 2-N-acetylglucosamine moiety on the value of the (Î± C 56.2) carbon chemical shift of the C2-position. The amino acid derivative was inactive on the Sk Br-3 (breast) and HT-29 (colon) human cancer cell lines and MA-104 kidney monkey cell line.